LncRNA PVT1 epigenetically silences miR-195 and modulates EMT and chemoresistance in cervical cancer cells. (9th August 2017) - Shen, Ching-Ju; Cheng, Ya-Min; Wang, Chiu-Lin
Abstract: The plasmacytoma variant translocation 1 gene (PVT1) is an oncogenic lncRNA with regulative effect on chemosensitivity in cervical cancer. However, the underlying mechanisms were not fully understood. In this study, HPV16 positive CaSki and SiHa cells were used as in vitro cell model. Knockdown of HPV16 E7 significantly inhibited PVT1 and restored miR-195 expression. PVT1 directly interacts with EZH2 and the complex anchors in the promoter region of miR-195. PVT1 overexpression resulted in increased H3K27me3 levels in the miR-195 promoter region, while PVT1 knockdown decreased H3K27me3 levels in the promoter region. In addition, PVT1 could competitively bind with miR-195. MiR-195 overexpression suppressed PVT1 expression in the cancer cells. Both PVT1 and miR-195 could inhibit paclitaxel (PTX) induced epithelial-to-mesenchymal transition (EMT) and also sensitize CaSki cells to PTX. Based on these findings, we infer that PVT1 could decrease miR-195 expression via enhancing histone H3K27me3 in the miR-195 promoter region and also via direct sponging of miR-195. In addition, the PVT1/miR-195 axis can modulate responses of the cancer cells to PTX via regulating EMT.